Mortgage fraud and organized crime in Canada: strategic intelligence brief - von Lampe, Klaus (Trends in organized crime, 2008)
Natasha Tusikov, Acting Manager, National Research and Methodology Development Unit, Criminal Intelligence Service Canada - Central Bureau, Intelligence Analysis and Knowledge Development Branch, November 2007 http://www.cisc.gc.ca/products_services/mortgage_fraud/document/mortgage_e.pdf